The Effects of Reading and Concept Map Teams Games Tournament Model Assisted by Picture Card and Snake Ladder on Students' Critical Thinking Skills - Widyatama, Angga Sofyana; Amalia, Andin Vita (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
This study aims to determine the significant effect of the application of the reading and map concept learning models teams games tournament with the help of picture cards and snake ladders on students' critical thinking skills on the material excretion system. This type of research is quasi experimental with a nonequivalent control group design using purposive sampling in class VIII D and class VIII E from the population in class VIII A to class VIII H. The research data were obtained from pretest and posttest scores and questionnaire sheets. The results of the t-test analysis related to critical thinking skills showed -0.13 in the initial data and 10.47 in the final data. Analysis of N-gain on increasing students' critical thinking skills results 0.80 (high) for the experimental class and 0.38 (moderate) for the control class. The results of the questionnaire sheet analysis showed a percentage of 89.30% with a very good category. Based on this it was concluded that learning using the reading and map concept team games tournament model with the help of picture cards and snake ladder on the excretion system material affects the improvement of students' critical thinking skills.